The impact of metabolic syndrome on serum total testosterone level in patients with erectile dysfunction. (June 2014) - Aslan, Yilmaz; Guzel, Ozer; Balci, Melih; Tuncel, Altug; Yildiz, Muslum; Atan, Ali
Abstract Objectives: To determine the association between metabolic syndrome (MetS) and serum testosterone levels (TT) in patients with erectile dysfunction (ED). Methods: This study included 280 ED patients above 40-years-of-age. Participants were divided into two groups according to 2005 criteria of International Diabetes Federation. The severity of ED was determined according to the International Index of Erectile Function-EF (IIEF-EF score; 0–10 severe ED, 11–25 mild to moderate ED). The severity of ED, serum TT levels and other MetS components were compared between the groups. Results: The mean age of the patients was 55.7 ± 8.2 years. One hundred eighteen patients (%42.1) had MetS. Sixty-eight patients with MetS (57.6%) and 71 patients without MetS (43.8%) had severe ED (p = 0.031). A total of 46 (16.4%) patients had hypogonadism. Hypogonadism was seen more prevalent in patients with MetS (22.9% vs. 11.7%, p = 0.013). Logistic regression analyses for ED risk factors demonstrated that abnormal FBG increased the relative risk of severe ED up to 10.7-fold (p < 0.001) but not presence of hypogonadism (p = 0.706). Conclusion: Metabolic syndrome was seen in almost half of the patients with ED. ED was more severe among MetS patients. Hypogonadism alone is a not risk factor for severe ED.